Physical Origin of General Oscillation of Structure, Surface Energy, and Electronic Property in Rutile TiO2 Nanoslab - He, T; Li, J. L; Yang, G. W (ACS applied materials & interfaces, 2012)
Titanium oxide (TiO2) nanostructures have been attracting consistent focus in the past few years because of their enhanced power in solar-energy conversion. Surface and interface play a crucial role in the determination of thermodynamic stability and electronic structure of TiO2 nanostructures. The rutile (110) nanoslab (NS) has been used as a common subject to investigate the surface relaxation, defect characters, molecule adsorption, and chemically dynamic reaction of TiO2 nanostructures. Up to date, a long-time standing issue in TiO2 NS, i.e., the general oscillation of structure, surface energy and electronic property with changing of NS thickness, has not been clear. We have presented a comprehensive investigation on the relationship between surface and oscillation behavior in the TiO2 (110) NS by the first-principles calculations accompanied with the wave function analysis. We clearly, for the first time, pointed out that the dipoles and surface states bonding induced by the surface–surface interactions are the physical origin of general oscillations in the TiO2 (110) NS. Our findings not only have a new insight into the basic interactions between surfaces in TiO2 nanostructures, but also provide useful information for tuning the photocatalytic and photovoltaic properties by surface design.